1988
DOI: 10.1007/bf00014534
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics and spatial variation of algae in relation to hydrology and sediment characteristics in the Okefenokee Swamp, Georgia

Abstract: In a 20-month study, phytoplankton and periphyton chl a, and dry mass of macroscopic algal aggregates in four marshes and a lake within the Okefenokee Swamp (Georgia, USA) were comparable to other wetlands and lake littoral areas. Chlorophyll levels in two marshes were inversely related to water level and phytoplankton at three marshes developed unimodal maxima following macrophyte dieback. Standing stocks in a vernally inundated marsh were greater than a nearby marsh which was permanently inundated; chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Equilibrium phosphate concentration of the sediment complex was elevated at the abandoned rookery, and levels of phytoplankton were correspondingly elevated. These field results are corroborated by results from laboratory experiments, which indicated that sediments from the abandoned rookery released more PO4-P to overiying water than sediments from other Okefenokee marshes, and overlying phytoplankton were then increased to greater levels (Schoenberg and Oliver 1988). Experimental enrichment of Okefenokee corrals corresponding to levels left after birds had abandoned the site caused elevation of zooplankton primary consumers.…”
Section: Possible Positive Feedbacks In the Systemsupporting
confidence: 58%
“…Equilibrium phosphate concentration of the sediment complex was elevated at the abandoned rookery, and levels of phytoplankton were correspondingly elevated. These field results are corroborated by results from laboratory experiments, which indicated that sediments from the abandoned rookery released more PO4-P to overiying water than sediments from other Okefenokee marshes, and overlying phytoplankton were then increased to greater levels (Schoenberg and Oliver 1988). Experimental enrichment of Okefenokee corrals corresponding to levels left after birds had abandoned the site caused elevation of zooplankton primary consumers.…”
Section: Possible Positive Feedbacks In the Systemsupporting
confidence: 58%
“…Fabre (1988) and Schomberg & Oliver (1988), showed that drawdown increased P release during refiling the reservoir. Within Embalse del Rio Tercero Reservoir, mineralization of sedimentary organic matter during drawdown was coupled with enhancement of nutrient cycling by breeding cattle in the newly developed prairies.…”
Section: Discussionmentioning
confidence: 99%
“…6A). As little as 1 7% of total bacterial biomass could be supported by aboveground lignocellulose inputs in summer months, although carbon sources such as algae and plant exudates are also available at this time of the year Hodson 1986, Schoenberg andOliver 1988). As much as 100% of bacterial biomass could be derived from lignocellulosic carbon during the winter.…”
Section: Discussionmentioning
confidence: 99%
“…(B) Comparison of protozoan and meiofaunal biomass predicted to be derived from microbially degraded lignocellulose (--) to protozoan and meiofaunal biomass determined from A TP measurements of water and sediments of Mizell Prairie from April 1982 to July 1983 (e; Moran et al 1987). Biomass attributable to bacteria (direct counts) and biomass attributable to algae (chlorophyll measurements; Schoenberg and Oliver, 1988) were substracted from total ATP biomass to calculate protozoan and smallanimal biomass. enfold increase in total bacterial carbon in Mizell Prairie from winter to summer (Moran eta!.…”
Section: Discussionmentioning
confidence: 99%